Clinical profile and management of ectopic pregnancy in patients with ectopic pregnancy at GMERS medical college and hospital Dharpur-Patan, North Gujarat region, India - Patel, Uday Mohanlal; Gandhi, Mayur Rajendra; Jani, Parul S.; Kakani, C. R.; Thakor, Nilesh (International Journal of Research in Medical Sciences, 2017)
Background: Ectopic pregnancy is assuming greater importance because of its increasing incidence and its impact on woman’s fertility. Objective: To study the clinical profile and management of ectopic pregnancies. Methods: This prospective study was conducted over one year from 1st January 2013 to 31st December 2013 for risk factors, mode of presentation, status at admission, diagnostic and treatment modalities and management of patients with ectopic pregnancy. Results: Over all mean rate of ectopic pregnancy has been found 11.41/1000 births. Out of total 52 cases 32 (64%) were referred while 20 (36%) were emergency cases. Out of 52 patients, 23 (44.23%) were from urban areas and 29 (55.77%) were from rural areas. Majority of the patients (51.97%) were in 26-30 years age groups. Gravida 3 had highest incidence (30.76%) of ectopic pregnancy. Maximum (50%) ectopic pregnancies were found in women with active married life of 5-10yrs. Out of total 52 cases, 44 (84.62%) were ruptured ectopic pregnancy cases. Ampulla was the most common site for tubal ectopic pregnancy (51.92%). Abdominal pain was the most common presenting symptoms (92.30%) followed by amenorrhoea in 84.61% cases. Majority of patients had history of infertility (42.30%) as a major risk factor. Laparoscopic management was done in 13 (25%) patients out of them lap. salpingectomy was done 9 (17.31% of total) and lap. Salpingostomy was done in 4 (7.69% of total) patients. Conclusion: Although ectopic pregnancy will never be completely prevented, but incidence can be reduced and much of the morbidity and mortalities can be minimised by prevention and efficacious diagnostic and interventional strategies aimed primarily at those women who are at high risk for the condition and taking precaution that woman who likely to become high risk are handled in such a way that the number of these high risk women are reduced.